The association of lifestyle physical activity, smoking and alcohol consumption practices on bone health status of postmenopausal chinese women in Kelantan - Wong, Agnes (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Although higher participation of intense and mechanical-loading physical activity (PA) yields significant osteogenic effects in maximizing bone mass devel?pment throughout lifespans, but specific types, intensity and frequency ofPA that could help to prevent an excessive bone loss during adulthood and aging is still limited, in particular among older populations in Asia. The aim of the present study was to examine the influence of habitual PA and other lifestyle practices on bone health status among postmenopausal Chinese women aged between 51 and 78 years in Kota Bharu, Kelantan. Several method assessments were used namely, a piloted questionnaires pertaining to general characteristics, general health status, lifestyle P A, smoking and alcohol consumption practices, as well as dietary behavioral practices were gathered. A piloted PA questionnaire for the past one-year was used to assess the habitual PA levels of two domains of leisure-based and household-based activities. Bone health profiles of these participants were measured at various skeletal sites of the total body, lumbar spine (L2- L4) and proximal femur using a dual energy X-ray absorptiometry device (DXA), as a criteria reference method for bone health assessment. The mean age of the participants was 57.3 years, with mean age since menopause of 7.6 years. Multivariate analysis of co-variance (ANCOV A) was carried-out to examirie these lifestyle practices on bone health profiles, after taking into account for other potential confounding factors such as age, age of menopause, types of menopause, and family history of osteoporosis, BMI, waist circumferences, and other dietary lifestyle practices. The findings found that postmenopausal Chinese women with higher daily PA levels both in leisure-time and household-time physical activity were significantly associated with higher BMD levels ofthe total body, proximal femur and lumbar spine (L2-L4) than that of those women of lower daily PA practices. In contrary, there was not significant association found between smoking status and alcohol consumption level on any bone health indices measured. The present findings showing that higher participation in daily PA with sufficient mechanical loading exerts significant beneficial impacts on bone health among postmenopausal Chinese women. Therefore, continuous encouragement of active lifestyle practices such as daily PA levels for at least 2 hours of moderate to highintense physical activity in a day should be highly encouraged among older populations in order to prevent an excessive bone loss during the late adulthood.